(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article discusses one of the main quality indicators of grain, grain moisture and grain moisture control, grain moisture measurement methods, the role and importance of grain moisture in processing, and analysis of measures to reduce electricity consumption.